Transforming information security : optimizing five concurrent trends to reduce resource drain - Moriarty, Kathleen M. (Emerald Publishing Limited, 2020)
The information security industry is undergoing a major change, forced by the rise of end-to-end encryption, encryption that cannot be intercepted, transport protocol stack evolution, "zero trust networks", and distributed computing. While we understand the logical connections between these trends, there is little analysis of all of these trends in combination. Examination of all five trends uncovers opportunities that not only improve the state of information security and the general posture, but also lead to resource reductions necessary for information security to be sustainable. In this exciting new book from security expert Kathleen M. Moriarty, the examination of all five trends uncovers opportunities to change the state of information security. Providing a unique perspective from the center of the debates on end-to-end encryption, Moriarty explores emerging trends in both information security and transport protocol evolution, going beyond simply pointing out today's problems to providing solutions for the future of our product space.
Includes index.
Keywords: Computer security.; Data protection.; Data encryption (Computer science); Computers, Security -- General.; Data encryption.; elektronické knihy; electronic books